PENGARUH CHATGPT DAN PROKRASTINASI AKADEMIK TERHADAP PRESTASI BELAJAR PERBANKAN DASAR DENGAN MEMODERASI INTERAKSI TEMAN SEBAYA - Natalia Natalia; Luqman Hakim (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study aims to measure the extent to which ChatGPT and academic procrastination influence Basic Banking learning achievement by moderating peer interaction. The sample used was class X Banking Service students of SMK Negeri 1 Kemlagi with a total of 62 students. Sampling was carried out using the Simple Random Sampling method. Data were analyzed using Multiple Linear Regression Analysis and Moderation Regression Analysis (MRA). The results of the study showed (1) ChatGPT had a significant positive effect on Basic Banking learning achievement, this was evidenced by the t count value > t table with a positive sign (3,133 > 1,671); (2) academic procrastination had a significant negative effect on Basic Banking learning achievement, this was evidenced by the t count value < t table with a negative sign (-4,344 < -1,671); (3) peer interaction cannot moderate the influence of ChatGPT on Basic Banking learning achievement, this is proven by the calculated t value > t table with a negative sign (-0,464 > -1,672); (4) peer interaction moderates the influence of academic procrastination on Basic Banking learning achievement, this is proven by the calculated t value > t table with a positive sign (3,760 > 1,672). However, this study has limitations in the number of samples and scope which only covers one school, so the results cannot be generalized widely.